Evaluation of Aids and hepatitis-B knowledge and job satisfaction among hairdressers and barbers in Turkey - Müjde Kerkez; Rabia Sohbet; Canan Birimoglu Okuyan (Universidade Estadual de Maringá, 2022)
Blood-borne viruses, including the human immunodeficiency virus and hepatitis B virus, have certain common epidemiological characteristics and these viruses infect millions of people worldwide. This study aimed to determine the job satisfaction and the level of knowledge and practices regarding infectious diseases of employees working as hairdressers and barbers. This descriptive and cross-sectional study comprised 1200 hairdressers and barbers. The study sample comprised 628 people who consented to participate in the study. The mean age of the participants who participated in the study was 28, 13 ± 6. 9 years. The mean job satisfaction score of the participants was 3.85 ± 0.58. The job satisfaction score was found to be higher among those with sufficient knowledge of hepatitis B (p < 0.005). Employees should be provided performance trainings to achieve job satisfaction. It is recommended that employees be encouraged to wear gloves and gowns to protect their health and prevent contamination.